Marine Disaster Risk Management: The Contribution of Maritime Engineering (Collaborate Engineering Daily Book Series, 2025)
Marine disasters such as tsunamis, tropical storms, coastal flooding, and coastal abrasion are serious threats to coastal communities, maritime infrastructure, and economic activity. Marine disaster risk management is very important to minimize its negative impact. Marine engineering plays a strategic role in risk mitigation through the design of coastal protection structures, such as sea walls, breakwaters, and seawalls, as well as hydrodynamic modeling to predict the behavior of waves, currents, and tides in extreme conditions. In addition, marine engineering supports the development of sensor, radar, and satellite-based marine disaster warning and monitoring systems, enabling rapid and precise decision-making. With the integration of structural engineering, scientific modeling, and monitoring technology, marine disaster risk management becomes more comprehensive, proactive, and sustainable. This article discusses the contribution of marine engineering in minimizing the risk of marine disasters and improving the safety and resilience of coastal areas. With the integration of structural engineering, scientific modeling, monitoring technology, and community participation, marine disaster risk management becomes more comprehensive, proactive, and sustainable. This article discusses the contribution of marine engineering in minimizing the risk of marine disasters and improving the safety, resilience, and sustainability of coastal areas.
Keywords: Maritime Engineering; Marine Disasters; Risk Management; Coastal Protection; Early Warning Systems; Community Mitigation